DEMOCRATIC POLITICAL CULTURE MODEL OF THE PEOPLE IN SONGKHLA PROVINCE - Kittikun, Monaek; Sitthiphataraprabha, Sitthipong (Journal of MCU Nakhondhat, 2025)
This research article is a qualitative study to analyzing the general conditions regarding problems and obstacles, examining the components, and develop a model of democratic political culture among the people of Songkhla Province. Data were collected from academics, government officials, election managers, national and local politicians, military personnel, police officers, businesspeople, media professionals, and members of the public. In-depth interviews were conducted with 27 persons, and Focus group discussions were conducted with 10. The research instruments used were interview guides, and the data were analyzed using descriptive analysis. The findings revealed that: 1) The general conditions concerning problems and obstacles related to the democratic political culture of the people in Songkhla Province revealed that Songkhla has a diverse political culture. Technological advancements have enabled groups of people to access information and exchange political opinions more easily and rapidly. There are also obstacles arising from the ineffective enforcement of laws by relevant agencies, which has allowed capitalist democracy to drive changes in the political culture. 2) The components of the democratic political culture among the people of Songkhla Province include respect for the rights and freedoms of others, respect for differing opinions, and participation in democratic processes. Additional components include capitalism, politically active leadership, and political communication technologies. and 3) The model of democratic political culture among the people of Songkhla Province is conceptualized through the PCPM Model, which consists of the following key components: P = Participation in Politics, C = Confidence in the Democratic System, P = Promoting Education and Political Literacy, and M = Media and Communication.